PENYELESAIAN SENGKETA BISNIS MELALUI ONLINE DISPUTE RESOLUTION DAN PEMBERLAKUANNYA DI INDONESIA - Bambang Sutiyoso (Fakultas Hukum Universitas Gadjah Mada, 2008)
This paper is an attempt to discuss some issues concerning of business settlement via Online Dispute Resolution (ODR), Online Arbitrate Agreement, Online Arbitrate Procedure, Online Arbitrate Judgment, and examining the practice of the ODR in Indonesia. This description is an attempt to give comprehensive view about ODR and how the law will be used to mediate the civil dispute using the Internet media and alternative possibility resolve civil conflict in the Indonesian society. In the future, this discussion will open a new way in facilitating Indonesian people, especially that are seeking the justice provision, in the resolving their dispute using via the ODR.